Persepsi Penonton pada Film “27 Steps of May” - Melly Dwina; Nyoman Puspadarmaja (Bandung Conference Series: Journalism, 2023)
Abstract. Film is a series of moving images and produces a story called a movie. The relationship between communication and film is that with communication, the process of making a film will be easier because it can avoid miss communications between individuals in the process of making a film. The film "27 Steps Of May" is an Indonesian drama film directed by Ravi Bhawani and written and produced by Rayya Makarim. The film discusses mental health and sexual violence which are widely practiced in everyday life and result in serious trauma for victims. This study aims to determine the audience's perception after watching the film "27 Steps Of May" and with this film, the audience is expected to have insight or learning from each scene. The researcher uses the agenda setting theory developed by McCombs and Shaw (1972) and discusses perceptual processes such as physical, physiological, and psychological processes in order to provide clear meaning for society. This study uses qualitative methods in descriptive form and uses triangulation techniques to examine data such as open coding, axial coding, and selective coding stages. The result of this study is that the perception process triggers the audience of the film "27 Steps Of May" so that they have the perception that with the existence of mass media such as films, the audience gets information or messages in every scene so that the audience can share information with other individuals to dare to start interacting and trying to get up despite having trauma in his life. Abstrak. Film merupakan suatu rangkaian dari gambar yang bergerak dan menghasilkan sebuah cerita yang disebut movie. Keterkaitan komunikasi dengan film yaitu dengan adanya komunikasi proses pembuatan film akan lebih mudah karena dapat menghindari miss communication antar individu dalam proses pembuatan film. Film “27 Steps Of May” salah satu film drama Indonesia yang disutradarai oleh Ravi Bhawani dan ditulis diproduksi oleh Rayya Makarim. Film tersebut membahas tentang kesehatan mental dan kekerasan seksual yang banyak dipraktikkan dalam kehidupan sehari-hari dan mengakibatkan trauma serius bagi para korban. Penelitian ini bertujuan untuk mengetahui persepsi penonton setelah menonton film “27 Steps Of May”dan dengan adanya film tersebut maka penonton diharapkan mempunyai wawasan atau pembelajaran dari setiap adegan yang ada. Peneliti menggunakan teori agenda setting yang dikembangkan oleh Mc Combs dan Shaw (1972) dan membahas proses-proses persepsi seperti proses fisik, fisiologis, dan psikologis agar memberikan makna yang jelas bagi masyarakat. Penelitian ini menggunakan metode kualitatif dalam bentuk deskriptif dan menggunakan teknik triangulasi untuk memeriksa data seperti tahapan open coding, axial coding, dan selective coding. Hasil penelitian ini adalah proses persepsi memicu penonton film “27 Steps Of May” sehingga memiliki persepsi bahwa dengan adanya media massa seperti film penonton mendapatkan informasi atau pesan dalam setiap adegan yang ada sehingga penonton dapat berbagi informasi kepada individu lainnya untuk berani memulai berinteraksi dan berupaya untuk bangkit walaupun memiliki trauma dalam hidupnya.